Left ventricular diastolic function during pregnancy: insights from conventional and speckle tracking echo parameters. (14th October 2021) - Tryfou, E; Kostakou, P; Kostopoulos, V; Paraskevaidis, I; Olympios, C; Kouris, N
Abstract: Introduction: Profound changes occur in the cardiovascular system during pregnancy, regarding to induce cardiac pumping function. Although LV systolic and diastolic function have been thoroughly studied using conventional indices, speckle tracking parameters of cardiac function are not well described. Purpose: The aim of our study was to evaluate the LV diastolic function during an uncomplicated pregnancy using both traditional and newer speckle tracking parameters. Methods: We prospectively enrolled 40 consecutive pregnant women in whom serial echocardiographic evaluation was performed in each pregnancy trimester (1st: 8th–12th week, 2nd: 22th–26th week, 3rd: 32–36th week) and 6 months after delivery. Mitral inflow velocities (E, A), mitral annulus TDI velocities (E', A'), ratio E/A and E/E' and untwisting velocity rate were measured after cautious selection of studies with legible images in. Results: The peak E transmitral inflow velocity during early diastole decreased significantly during pregnancy especially between 2nd and 3rd trimester and increased again postpartum (p1-2=0.475, p2-3<0.05 p3-4<0.05). The peak A flow velocity during atrial contraction did not change significantly during pregnancy (p1-2=0.333, p2-3=0.952, p3-4=0.989). As a result, E/A ratio was decreasing as pregnancy was advancing (p1-2=0.964, p2-3<0.05, p3-4=0.240). TDI E' early diastolic velocity was decreased especially in the 3rd trimester and recovered postpartum (p1-2=0.138, p2-3<0.01, p3-4<0.01) while E/E' ratio was increased especially in the 2nd trimester (p1-2<0.05, p2-3=0.572, p3-4=0.021, p1-4=0.383) and also recovered postpartum. Peak untwisting velocity rate demontrated a progressive decrease during pregnancy, although not statistically significant. There was a trend towards recovery in the puerperium (p1-2=0.072, p2-3=0.679, p3-4=0.052, p1-4=0.929) (Table 1). Conclusion: Our study demonstrated that diastolic function seems to be impaired during an uncomplicated pregnancy. However all the conventional and newer speckle tracking indices of diastolic function remain in normal range. Postpartum appears to be a recovery process in all parameters. Funding Acknowledgement: Type of funding sources: None.